Preservation of β-Cells as a Therapeutic Strategy for Diabetes - Taneera, Jalal; Saber-Ayad, Maha M. (Hormone and Metabolic Research, 2024)
The preservation of pancreatic islet β-cells is crucial in diabetes mellitus, encompassing both type 1 and type 2 diabetes. β-cell dysfunction, reduced mass, and apoptosis are central to insufficient insulin secretion in both types. Research is focused on understanding β-cell characteristics and the factors regulating their function to develop novel therapeutic approaches. In type 1 diabetes (T1D), β-cell destruction by the immune system calls for exploring immunosuppressive therapies, non-steroidal anti-inflammatory drugs, and leukotriene antagonists. Islet transplantation, stem cell therapy, and xenogeneic transplantation offer promising strategies for type 1 diabetes treatment. For type 2 diabetes (T2D), lifestyle changes like weight loss and exercise enhance insulin sensitivity and maintain β-cell function. Additionally, various pharmacological approaches, such as cytokine inhibitors and protein kinase inhibitors, are being investigated to protect β-cells from inflammation and glucotoxicity. Bariatric surgery emerges as an effective treatment for obesity and T2D by promoting β-cell survival and function. It improves insulin sensitivity, modulates gut hormones, and expands β-cell mass, leading to diabetes remission and better glycemic control. In conclusion, preserving β-cells offers a promising approach to managing both types of diabetes. By combining lifestyle modifications, targeted pharmacological interventions, and advanced therapies like stem cell transplantation and bariatric surgery, we have a significant chance to preserve β-cell function and enhance glucose regulation in diabetic patients.
Keywords: stem cells; islet transplantation; cytokine antagonists; immunomodulators; antidiabetic medications